Physically Detachable and Operationally Stable Cs2SnI6 Photodetector Arrays Integrated with µ‐LEDs for Broadband Flexible Optical Systems. Issue 17 (20th March 2022) - Krishnaiah, Mokurala; Kim, Seungyeob; Kumar, Ajit; Mishra, Dhananjay; Seo, Seung Gi; Jin, Sung Hun
Abstract: With the surge in perovskite research, practical features for future applications are desired to be secured, but the reliability of the materials and the use of hazardous Pb are longstanding problems. Here, an air‐stable Cs2 SnI6 (CSI) is prepared via diluted hydriodic acid solvent‐based precursor optimization during scalable hydrothermal growth. Materials characterization is performed using various elemental peak analyses and crystallographic identification. The resulting CSI exhibits long‐term operating stability over 6 months, i) at elevated temperatures, ii) in ambient air, and iii) under light illumination from UV to near‐infrared. More importantly, to demonstrate an intriguing class of applications up to system level, physically detachable CSI photodetector arrays (PD‐arrays), integrated with micro‐light‐emitting‐diodes (μ‐LEDs) arrays, are successfully fabricated. In addition, 3 × 3 flexible CSI PDs are fully operational, even in air, and their spatial uniformity in pixels is quantitatively evaluated. The charge‐transport mechanisms of the CSI PDs under light and elevated temperature are assessed via temperature‐dependent characterization from 148 to 373 K, implying the involvement of 3D variable‐range hopping. Multicycle evaluation of the CSI PD‐arrays confirms their operational stability in AC and DC modes, demonstrating this platform's potential benefit for wireless optical interconnection in advanced Si technology. Abstract : Air‐stable Cs2 SnI6 (CSI) particles via hydriodic acid precursor optimization are reported. For system‐level demonstration, physically detachable 3 × 3 photodector (PD) arrays, assembled with micro‐light‐emitting‐diodes (µ‐LEDs) as light sources, are demonstrated to cover the broadband spectrum of UV–visible–near‐Infrared (NIR) and hold great promise for future wireless optical interconnection.